Islamic Religious Education Learning Based on Digital Literacy to Make Students Literate in Religious Information - Husnizar, Husnizar; Hadi, Abdul; Yusuf, M.; Muhajir, Muhajir; Imran, Imran (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to describe digital literacy-based Islamic Religious Education (PAI) learning to foster students' literacy in religious information. The research method used is a qualitative library research approach. Data were collected from various written sources such as books, scientific journals, articles, and other relevant documents. Data analysis techniques employed content analysis and critical analysis to examine the concepts, strategies, and implications of integrating digital literacy into PAI learning in depth. The findings indicate that: 1) Integrating digital literacy into PAI is essential to build students’ immunity against religious hoaxes through a paradigm reorientation, where PAI serves as an “immunity laboratory”; 2) An effective implementation strategy is the blended learning model integrated with critical analysis of social media content; 3) The success of implementation depends on strengthening the digital competency of PAI teachers, who must transform from “sources of knowledge” to “digital content curators.” The significance of this study lies in providing a conceptual and strategic framework to bridge the gap between students’ digital reality and conventional PAI learning practices, thereby enhancing students' ability to filter, analyze, and responsibly engage with religious information in digital spaces.